Environmental Virtue Ethics and the Sources of Normativity - Michał Piekarski (Studia Ecologiae et Bioethicae)
This article is an attempt to identify the sources of normativity in virtue ethics. The starting point for the analyzes presented here is the book by Dominika Dzwonkowska Environmental virtue ethics. In § 1, I present the basic theses and assumptions of this approach to ethics. Then, with reference to the concept of the moral subject proposed by Dzwonkowska, I ask whether it constitutes the primary source of normativity (§ 2). I argue that environmental virtue ethics can be ascribed to arguments shared by supporters of the so-called constitutive arguments in metaethics (§ 3). Their position is based on the recognition that moral norms, obligations, etc., derive from the constitutive features of the subject. I call such an approach internalist and contrast it with the non-internalist approach, the outline of which I propose in § 4. In the Conclusion, I suggest that the pragmatic considerations and conservatism of researchers speak in favor of the internalist approach.